Enhancing the assessment of learning in Australian higher education : biological sciences. - Krause, Kerri-Lee; Harris, Kerri-Lee; Garnett, Robin; Gleeson, Dawn; Peat, Mary; Taylor, Charlotte (Carrick Institute for Learning and Teaching in Higher Education, 2007)
The aims of the project were: to gain insights and examples of good assessment practice in the biological sciences from tertiary educators, students, recent graduates and employers; to use the professional expertise of the project team to build on these insights and examples and to develop resources that would enhance assessment; to design curriculum-level resources and frameworks for use in the biological sciences; and, to strategically disseminate these resources and engage the disciplinary community in ongoing discussion of assessment by means of a website, seminars and consultations in every State. [p.1]